Lead Cap Use in Interventional Cardiology: Time to Protect Our Head in the Cardiac Catheterisation Laboratory? - Yasar Sattar; Prasanna M Sengodan; Mustafa Sajjad Cheema; Nismat Javed; Shoaib Ashraf; Sadaf Fakhra; Anas Alharbi; Moinuddin Syed; Mahboob Alam; Islam Y Elgendy; Affan Haleem; Akram Kawsara; et al. (Interventional Cardiology: Reviews, Research, Resources)
Background: Radiation exposure is an occupational hazard for interventional cardiologists and cardiac catheterisation laboratory staff that can manifest with serious long-term health consequences. Personal protective equipment, including lead jackets and glasses, is common, but the use of radiation protective lead caps is inconsistent. Methods: A systematic review qualitative assessment of five observational studies using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines protocol was performed. Results: It was concluded that lead caps significantly reduce radiation exposure to the head, even when a ceiling-mounted lead shield was present. Conclusion: Although newer protective systems are being studied and introduced, tools, such as lead caps, need to be strongly considered and employed in the catheterisation laboratory as mainstay personal protective equipment.